The Major Characters in Gillian Flinn Novel “Sharp Objects” (A Psychoanalysis Freud) - Banatul Qodariyah; Ainur Rohmah; Sugiyani Natalia (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2017)
This research is intended to find the psychological conflict faced by the major character in the Gillian Flinn novel. It is a content analysis study that belongs to qualitative research. The researcher read the novel several times to collect the data and also to analyze the data. It is done several times to get a deeper understanding of the information related to the psychological conflict in the novel. While reading the researcher give a code to the data for description the conflict. The analysis of this research is done using Freud’s theory of psychology, a psychoanalysis Freud. The result shows that there are two kinds of psychological conflicts in ‘Sharp Objects’ novel. They are approach-avoidance conflict and avoidance-avoidance conflict that describing that all the characters have a conflict because of the id, ego, and superego are inconsistency condition.